PERCEPTIONS OF TEENAGE WOMEN ABOUT EARLY MARRIAGE IN BANGLADESH - Sultana, A. M.; Salam, A. M., (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Despite the alarming trend of increased marriage age in many societies, early marriage is still a serious issue in Bangladesh. The significant numbers of women being married before the age of 18. The study determines young women’s experience and perception of early marriage. Young married women’s perception and experiences were measured using a series of the statement. According to the results, the majority of the participants supported arranged marriage. The results also revealed that early marriage impact on decision making, education, unfulfilled dream, unwanted pregnancies, and marital satisfaction. Given that early marriage is a negative impact, a multidimensional approach is necessary to support and empower disadvantaged women.